"Seca, geada e fogo" : considerações sobre um desastre ambiental (Paraná, 1963) - Paixão, Letícia Aparecida da (2015)
This work has the intention to analyze the environmental disaster in Paraná in 1963. In that year, there was a long drought, followed by frost and forest fires that shook the Paraná's field, reaching tragic consequences, like the death of 110 people, thousands of homeless and the destruction of more than 600,000 acres of forests and plantations, as well as houses, farms and barns. The causes are complex and the conditions for triggering such a disaster were created in the process of transformation of state's landscape with colonization and introduction of coffee in the Pioneer North, which promoted large-scale deforestation and impoverishment of the soil. Because of the consequences generated by fires, the State's Government and the private sector proposed a number of remedial actions. Measures to assist the victimized population were influenced by political disputes evidenced by the political situation of that time that was marked by the conspiracy of a civilian-military coup and the US hegemony in Latin American countries. The study also reports the economic, social, health and environmental problems that Paraná's population had to deal with the occurrence of fires. The materials used for this research are the Paraná State official data, regional newspapers, magazines, private business reports and photographs. To better understand the theme and the environmental disaster concepts we used the theoretical and methodological references of Environmental History. Through its references, we expanded the study of man's relationship with the natural environment to comprehend the changes that occurred in the landscape and how these changes can influence the society directly. In short, we must take into account that such environmental disaster is the result of the relations of the inhabitants with their natural surroundings. It is important to know the historicity of these relations in order to understand the real extensions of this event and how it is inserted in a broader context, marked above all by the eradication of coffee plantations that had been occurring since the early 1960s and by the process of deforestation of the state's central region.